Interoperability Testing Guide for the Internet of Things - Castelo Branco, Karina da Silva; Dantas, Valéria Lelli Leitão; Carvalho, Liana Mara (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2024: Proceedings of the 30th Brazilian Symposium on Multimedia and the WebDO - 10.5753/webmedia.2024.242058, 2024)
The Internet of Things (IoT) has expanded the Internet by integrating smart objects, which when interconnected, can collect and share information to provide services. However, the intense data traffic and the diversity of interaction methods of smart objects, which vary based on the protocols and standards, bring several challenges for IoY Interoperability Testing. Such testing evaluates the capability of systems and devices to cooperate effectively. Regarding the challenges in IoT interoperability testing, we highlight the complexity of IoT architecture, the devices heterogeneity, and the guarantee of effective connectivity among the smart objects. In this context, this paper presents a interoperability testing guide for IoT. The guide was developed based on a literature review using systematic mapping and an analysis of real IoT environments. The guide’s evaluation consisted of two steps: (1) a structural assessment using the Technology Acceptance Model (TAM), and (2) a controlled experiment applying the guide to test a real IoT application.